Force short of war in modern conflict : jus ad vim - Galliott, Jai (Edinburgh University Press, 2019)
Jai Galliott explores the overarching phenomenon of how force short of war is being used in modern conflict, and how it impacts just war theory. He shows that we need to bring the rules of war into alignment with increasingly digital means of conducting kinetic warfare through the force short of war paradigm.